Analisis Kesalahan Penggunaan Fragesatz - Al-Thasyam, Ananda Nur Hazanah; Al-Ilmul, Syarifah Fatimah; Achmad, Abdul Kasim (Universitas Negeri Makassar, 2021)
The purpose of this research was to obtain the data of types of error within the usage of question sentences by the 12th Class Students of SMA Negeri 16 Makassar. The research was a descriptive qualitative research. The data was obtained through a writing test. The data source of this research was 12th Class students of SMA Negeri 16 Makassar. The data was obtained using total sampling. The amount of samples was 1 class which consisted of 36 students. The result of the data analysis showed that there were 203 errors in using the question sentences. There were 84 errors of W-questions, 63 errors of general questions, and 56 erros of sentence arangements. The error rate when using the question phrase for SMA Negeri 16 Makassar 12th Class is in the very high category.